Adoption of Preventive Measures After Returning to Work Among Workers Affected by De Quervain's Tenosynovitis. - Calvo-Cerrada, Beatriz; Martínez, José; Dalmau, Antonio (Journal of Occupational Rehabilitation, 2012)
Objectives To determine whether if there was any increase in preventive measures adopted following reincorporation to their jobs among workers affected by De Quervain's tenosynovitis (DQT), who were treated by surgical intervention. Methods Study subjects where those workers, members of a mutual health insurance scheme, who were operated on between June 2006 and June 2009 (n=52). For each worker we checked whether preventive measures had been taken in their workplace, both before their episode, and following reincorporation. The difference in proportions (DP) was calculated between the proportion of individuals with preventive measures after reincorporation and the proportion with preventive measures implemented prior to their surgical intervention, both globally and in terms of sociodemographic, occupational, and clinical variables. Results The proportion of workers with preventive measures adopted following reincorporation to their job was higher than the proportion with preventive measures prior to their surgical intervention (DP = 23.1 %; 95 %CI: 6.4-39.7 %). The risk factors associated with the greatest change in preventive measures were repetitive movements (DP = 25.6 %; 95 %CI: 6.1-45.1 %) and awkward postures (DP = 40 %; 95 %CI: −22.9 to 100 %). Conclusions Despite the increased proportion of workers with preventive measures implemented in their workplace following reincorporation to the job, there is a lack of information and of adoption of ergonomic preventive measures specific to this pathology. Implementation of ergonomic programs could reduce incidence of musculoskeletal disorders such as DQT, and would thus increase productivity, efficiency and worker satisfaction, while diminishing sick leave episodes, and the associated costs and relapses.